Subunit exchange of multimeric protein complexes. Real-time monitoring of subunit exchange between small heat shock proteins by using electrospray mass spectrometry. - Sobott, F; Benesch, J; Vierling, E; Robinson, C (2002)
The subunit exchange of the small heat shock proteins (sHSPs) PsHSP18.1 from pea and TaHSP16.9 from wheat has been monitored in real-time using nanoelectrospray mass spectrometry. By preserving the noncovalent interactions between subunits in the mass spectrometer, we show that these proteins are dodecameric. After mixing PsHSP18.1 and TaHSP16.9, a distribution of heterododecamers is formed. A comparison with spectra obtained from statistical modeling demonstrates that after equilibration the distribution of these heterocomplexes is governed by the starting ratio of the two components rather than an inherent preference for certain stoichiometries. This finding suggests that the two different sHSP subunits interact in a very similar manner. Following the kinetics of this reaction by mass spectrometry reveals that exchange proceeds via sequential incorporation of subunits with dimeric species being the principal units of exchange. Therefore, we conclude that sHSP complexes are in rapid dissociation/reassociation equilibria with suboligomeric forms. More generally, these experiments illustrate a powerful approach for the real-time analysis of the evolution of transient species and their relative populations during the subunit exchange of multimeric protein complexes.